The ABO system blood group determination in genetics class: ABO system blood group determination in genetics class - Ulandari, Eva Yasin; Maulina, Alfika Cahaya; Khimalaya, Anifia (Tropical Genetics, 2025)
This study aims to determine the blood type of genetics class students based on the ABO system. Blood type is a grouping of human blood based on the presence of agglutinogen on the surface of red blood cells and agglutinin in blood plasma. The activity was carried out in the laboratory of the Faculty of Tarbiyah and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, using the slide test method using Anti-A, Anti-B, and Anti-AB reagents. The results of the observation showed that the majority of students had blood type O (63%), while blood types A (18%), B (9%), and AB (9%). This examination utilizes the principle of agglutination, where a clotting reaction occurs if agglutinogen on red blood cells reacts with the relevant agglutinin in the reagent. Determination of blood type is very important for blood transfusions, organ transplants, and medical identification. This study provides students with a practical understanding of the blood type examination procedure and its significance in the health sector.